Economic Objectivity and Its Discontents: Reflections on Marx, Adorno and Utopia - Coe, Samuel (Sociologija. Mintis ir veiksmas, 2017)
This article seeks to interpret the meaning of communism as a negative utopian possibility; one that continually negates the present on the basis of that which ought to be different yet, despite its injustice, is proclaimed as truth. In the first section, through the prism of Adorno’s negative dialectics, Marx’s materialism is explored and criticised on the basis of the epistemological certainty that it assumes. In the process, the concept of class in particular will be scrutinised. Next, I draw on economic objectivity theory in order to formulate a conception of class that avoids the assigning of ontological value, and instead appears as a negative consequence of the false society. In the final section, I outline my understanding of communism as negative utopia, and explore how this may translate into a theory of praxis.